DNA repair - Campbell, Judith L.; Modrich, Paul (Methods in enzymology ;, 2006)
This volume emphasizes the intracellular consequences of DNA damage, describing procedures for analysis of checkpoint responses, DNA repair in vivo, replication fork encounter of DNA damage, as well as biological methods for analysis of mutation production and chromosome rearrangements. It also describes molecular methods for analysis of a number of genome maintenance activities including DNA ligases, helicases, and single-strand binding proteins. *Part B of a 2-part series *Addresses DNA maintenance enzymes *Discusses damage signaling *Presents In vivo analysis of DNA repair *Covers mutation and chromosome rearrangements.